TEACHING WRITING NARRATIVE TEXT USING TWO STAY TWO STRAY (TSTS) METHOD - Lina Nuraeni; Gartika Pandu Bhuana (PROJECT (Professional Journal of English Education), 2020)
Writing is part important of language. One important skill that should be mastered by the students. The fact show that most of the student find the difficulties in writing. The problems are related to their motivation and technical problem. The method is belief to be able to improve students writing skill. Therefore, the aims of the research is to investigate the application of Two Stay Two Stray (TSTS) method to improve students writing ability.This research used quantitative method.The population of this research was all tenth grade students at one of vocational schools in Cimahi. The sample was eightheen students of class X TKJ. The instrument used test.The result showed that the mean scores of pretest was 63.94 and of posttest was 73.88. From this data it can be concluded after students learned writing narrative text using Two Stay Two Stray (TSTS) method, their writing skill were improved.